The Role of High Religious Courts in The Bengkulu Area in Safeguarding Children's Interests Regarding Post-Divorce Living Expenses and Civil Rights - Pian, Happy; Mukhlas, Oyo Sunaryo; Arifin, Tajul; Saebani, Beni Ahmad; Ridwan, Ahmad Hasaan; Abdulah Pakarti, Muhammad Husni (Universitas Islam Sultan Agung, 2023)
This research aims to examine the legal process carried out by the Bengkulu Religious High Court in ensuring the living expenses of children after their parents' divorce. This study is qualitative research with a normative legal approach. Primary data comes from laws, court decisions related to children's rights post-divorce, and children's civil rights, while secondary data is obtained from books, online media, and journals with the same relevance. In exercising its authority, the Bengkulu Religious High Court prioritizes the principle of justice by maintaining the interests of the child, as well as the principles of balance and proportionality. However, there are several challenges such as the lack of public understanding of children's rights and obstacles in the implementation of Religious High Court decisions regarding the enforcement of children's civil rights. More intensive efforts are needed to provide the public with an understanding of children's rights and to improve the quality of enforcement of Religious High Court decisions to ensure optimal protection of the child's interests following their parents' divorce.